Political views, morality, and attitudes toward marijuana legalization - Dias, Rodrigo da Silva (2017)
In this paper, we examine why attitudes toward marijuana legalization are split along ideological lines. In a survey, we found that conservatives were more likely to oppose this policy partly because of their greater reliance on the authority and purity foundations of morality. Curiously, concerns about harm were found to play no role in determining attitudes toward marijuana legalization, even though those who were against this policy frequently explained their views with harm-related accounts. In an experiment, we found that opponents of legalization were more likely to adopt a more favorable view towards it when exposed to arguments and sources that were consistent with the authority and purity dimensions of morality. Precisely, subjects who initially opposed legalization were more likely to change their attitudes when exposed to arguments that were based on the purity (vs. harm) foundation of morality, and when they were led to believe that these arguments were given by religious (vs. business) leaders.